Evaluation of remote sensing techniques-based water quality monitoring for sustainable hydrological applications: an integrated FWZIC-VIKOR modelling approach - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
Evaluation of remote sensing techniques-based water quality monitoring for sustainable hydrological applications: an integrated FWZIC-VIKOR modelling approach by Alamoodi, Abdullah Hussein